Maximizing the safety of nonsteroidal anti-inflammatory drug use for postoperative dental pain: an evidence-based approach. - Ong, K. S. (2003)
This article reviews the use of nonsteroidal anti-inflammatory drugs (NSAIDs) for postoperative dental pain. An evidence-based approach is used to evaluate the clinical studies to date on the safe use of these drugs in dental patients. No drugs are without adverse effects or are perfectly safe, but their safe use in clinical practice would entail maximizing the therapeutic efficacy and minimizing the adverse effects. Therapeutic recommendations are made after reviewing the evidence for the safe use of NSAIDs in postoperative dental pain.